High-performance thermoelectrics and challenges for practical devices - Yan, Qingyu; Kanatzidis, Mercouri G. (Nature materials, 2022)
Thermoelectric materials can be potentially employed in solid-state devices that harvest waste heat and convert it to electrical power, thereby improving the efficiency of fuel utilization. The spectacular increases in the efficiencies of these materials achieved over the past decade have raised expectations regarding the use of thermoelectric generators in various energy saving and energy management applications, especially at mid to high temperature (400–900 °C). However, several important issues that prevent successful thermoelectric generator commercialization remain unresolved, in good part because of the lack of a research roadmap. Thermoelectric materials can generate energy from a heat differential. This Review provides an overview of mid- to high-temperature thermoelectrics, their application in modules, and the issues that need to be addressed to enable commercial implementation of state-of-the-art materials.